Identification and characterization of resistance to cowpea aphid (Aphis craccivora Koch) in Medicago truncatula - Kamphuis, L.; Gao, L.; Singh, Karambir (BioMed Central Ltd, 2012)
Background: Cowpea aphid (CPA; Aphis craccivora) is the most important insect pest of cowpea and also causes significant yield losses in other legume crops including alfalfa, beans, chickpea, lentils, lupins and peanuts. In many of these crops there is no natural genetic resistance to this sap-sucking insect or resistance genes have been overcome by newly emerged CPA biotypes. Results: In this study, we screened a subset of the Medicago truncatula core collection of the South Australian Research and Development Institute (SARDI) and identified strong resistance to CPA in a M. truncatula accession SA30199, compared to all other M. truncatula accessions tested. The biology of resistance to CPA in SA30199 plants was characterised compared to the highly susceptible accession Borung and showed that resistance occurred at the level of the phloem, required an intact plant and involved a combination of antixenosis and antibiosis. Quantitative trait loci (QTL) analysis using a F 2 population (n = 150) from a cross between SA30199 and Borung revealed that resistance to CPA is controlled in part by a major quantitative trait locus (QTL) on chromosome 2, explaining 39% of the antibiosis resistance. Conclusions: The identification of strong CPA resistance in M. truncatula allows for the identification of key regulators and genes important in this model legume to give effective CPA resistance that may have relevance for other legume crops. The identified locus will also facilitate marker assisted breeding of M. truncatula for increased resistance to CPA and potentially other closely related Medicago species such as alfalfa.